Pandemic myths in Indonesia culture and trust in official government information - Agus Setianto, Widodo; Sulhan, Muhamad; Mutia, Lidwina; Tania, Syaifa (International Journal of Communication and Society, 2024)
Multicultural communities in Indonesia produce mythologies related to disease outbreaks. This study aims to map such myths and their impact on trust in COVID-19 information, assuming that trust in the myths influences trust in COVID-19 information. This research is descriptive and qualitative in nature. Data consist of big data and the results of focus group discussions (FGDs) involving participants from three generations, i.e., baby boomers, millennials, and Gen Z, in three regions. Cross-analyses were performed to examine the data. The results of the big data analysis uncover the myths about the spread, detection, prevention, and treatment of COVID-19. Likewise, the FGD analysis shows myths and superstitions around the COVID-19 pandemic, which could be prevented through religious and cultural rituals. The firm belief in the myths and poor public communication by the authorities created ambiguity. The public believes more in myths than the official information. The findings of this study can inform the formulation of culture-based health communication strategies and the optimization of public communications in a health crisis like the COVID-19 pandemic.